A Baseline Study on the State of Local Climate Change Expenditure Tagging (CCET) in the Philippines - Asuncion, Xavier Venn; Cortel, Eleangel Dawn (Philippine Journal of Public Administration; Vol 68 (2024), 2024)
Local government units (LGUs) in the Philippines are situated at the forefront of climate change action. As they translate local plans into investment programs, LGUs are required to implement climate change expenditure tagging (CCET) to track budgeted items related to climate adaptation and mitigation. However, numerous LGUs in the Philippines have faced challenges in achieving sufficient compliance with CCET. This study, therefore, aims to contribute to this area by assessing the state of local CCET and subsequently identifying institutional and policy recommendations to improve its implementation. Using the  evaluation criteria developed by the Organization for Economic Cooperation and Development (OECD), this study employs a qualitative descriptive design involving document analysis, literature review and key informant interviews (KII). In general, the findings highlight the need for supporting legislation to ensure sustainability and propose an expansion of the tagging mechanics. This expansion may involve indicating financing sources, integrating adaptation and mitigation objectives within programs, projects, and activities (PPA), applying degrees of relevance through corresponding weights, accounting for negative expenditures, and tracking PPAs’ alignment with the five comprehensive development plan (CDP) sectors. To improve implementation effectiveness and efficiency, integrating CCET across LGUs’ planning, budgeting, and legislative functions is recommended, alongside institutionalizing administrative reforms for sufficient institutional capacities for CCET implementation.